An efficient intra-mode decision method for HEVC. Issue 6 (September 2016) - Hong, Seungbeom; Yang, Dongjun; Park, Byungkil; Yu, Sungwook
Abstract This paper proposes a new intra-mode decision method for HEVC. The proposed method makes use of the characteristics of some special modes that belong to both rough mode decision mode set and most probable mode set. It also improves the coding efficiency by adaptively applying different algorithms depending on the prediction unit size. Not only the luma components but also the chroma components are considered in this paper. In the intra-coding process for the chroma components, the proposed method changes the examination order and makes efficient use of the spatial correlation and coded block flag information. As a result, the proposed method shows significantly better performance compared to other intra-mode decision methods.